Personality Characteristics of Preschool Education Students with Different Levels of Emotional Intelligence - Koltunovych, Tetiana; Polishchuk, Oksana (LUMEN Publishing House, 2019)
The aims of this paper were to explore the influence of personality characteristics on students’ emotional intelligence. The study involved 87 university students (future preschool teachers). The sample is homogeneous. The “Emotional Intelligence” test (EmIn) (D. Lioussine), “The Big Five Personality Test” (5PFQ), “Test of empathic abilities level” by V. Boyko were employed. Methods of descriptive statistics, Spearman correlation analysis, Kruskal-Wallis one-way analysis of variance and structural analysis (by A. Karpov) were used. Mathematical data processing and graphical presentation of the results were carried out using the computer software package of statistical software SPSS 17.0. The results of this study confirm the suggested assumptions about the existence of reliable statistically significant relationships between the emotional intelligence, its components and students’ personal characteristics, and dependence of the emotional intelligence level from the peculiarities of the personality characteristics structural organization (p≤0.01). The elucidation of these regularities can be used to improve the psychological techniques of the development and correction of emotional intelligence among preschool education students.
Keywords: emotional intelligence, extraversion-introversion, affection-alienation, self-control-impulsivity, emotional instability-emotional, stability expressiveness-practicality, empathy